3D hierarchical tubular micromotors with highly selective recognition and capture for antibiotics. Issue 5 (21st January 2020) - Bing, Xingmei; Zhang, Xiaolei; Li, Jia; Ng, Dickon H. L.; Yang, Wenning; Yang, Jie
Abstract : Self-propelled micro/nanomotors attract a great deal of attention from the scientific community due to their great potential in environmental and biomedical applications. Abstract : Self-propelled micro/nanomotors attract a great deal of attention from the scientific community due to their great potential in environmental and biomedical applications. Here, molecularly imprinted magnetic micromotors with highly selective recognition and capture for antibiotics are presented. Such micromotors, powered by local fuel and with precise trajectory control over the self-propulsion direction, exhibit a unique 3D hierarchical tubular structure constructed by a combination of the biomass route and atom transfer radical polymerization (ATRP). Each component of such a hierarchical structure performs its own function: Br–MgAl layered double hydroxide (LDH) nanosheets as the initiator for ATRP to selectively recognize target molecules, Mn3 O4 nanoparticles as the catalyst for H2 O2 decomposition to generate oxygen bubbles for self-propulsion, and Fe3 O4 nanoparticles as the magnetic component for magnetic orientation and recycling. Due to the synergetic effects of self-propelled movement and highly exposed selective recognition sites from molecularly imprinted LDH nanosheets, such micromotors can rapidly recognize, capture and remove target antibiotics from water. The maximum doxycycline (DC) adsorption capacity of micromotors is up to 224.2 mg g −1 in the presence of 2% H2 O2, which is 1.6 times greater than their non-micromotor counterparts. More importantly, these micromotors can be quickly recycled by magnetic separation. This study provides a new insight for designing novel molecularly imprinted micromotors for water treatment.